ANALISIS PENGGUNAAN APLIKASI RAPOR KURIKULUM 2013 BAGI GURU SEKOLAH DASAR KECAMATAN WONOPRINGGO - Suryaningtyas, Dwi; Wakhyudin, Husni; Priyanto, Wawan (JURNAL SINEKTIK, 2018)
This study aims to find out and analyze the use of 2013 Curriculum report application for Elementary School teachers in Wonopringgo District, Pekalongan Regency. This type of research is a qualitative descriptive research with purposive sampling sampling technique. That is by collecting data through interviews, distributing questionnaires (questionnaires) and filling out observation sheets. The subjects of this study were teachers of class I, III, and IV SDN 01 Rowokembu, SDN 01 Wonopringgo, SDI Terpadu Gondang, SDN 02 Sastrodirjan, SDN 02 Galang pengampon, SDN Surobayan. The results of this study indicate that the use of the 2013 Curriculum report card application is actually not required or required by the central government (Ministry of Education and Culture). Existing applications are applications for individual projects or groups of people. The average Primary School teacher in Wonopringgo District has used the application either independently or with the help of other teachers. From the distribution of questionnaires, the results showed that the report card application was suitable for use by elementary schools throughout Indonesia.